Economics of Maritime Business - Ma, Shuo, 1955- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
"This book provides a comprehensive introduction to the economics of the business of maritime transport. It provides an economic explanation of four aspects of maritime transport, namely, the demand, the supply, the market and the strategy The book first explains why seaborne trade happens and what its development trends are; it then analyses the main features of shipping supply and how various shipping markets function; the book finally addresses the critical strategic issues of the shipping business. The full range of different types of shipping are covered throughout the chapters and cases. The book combines the basic principles of maritime transport with the modern shipping business and the latest technological developments, particularly in the area of digital disruption. The ideas and explanations are supported and evidenced by practical examples and more than 160 tables and figures. The questions posed by the book are similar to those that would be asked by the students in their learning process or the professionals in the business environment, with the answers concentrating on the reasons for what has happened and will happen in the future rather than merely fact-telling or any specific forecast. The book is most suited for students of shipping-related disciplines, and is also a valuable reference for maritime professionals"--
OCLC-licensed vendor bibliographic record.
Keywords: Shipping; Merchant marine -- Management; Management -- Technological innovations; BUSINESS & ECONOMICS / General